The role of subtitled movies in enhancing English language skills: postgraduate students' perceptions and motivation - Kamaruddin, Raihannah Khairyn; Azizul Hassan, Aini Faridah (Universiti Teknologi MARA, 2025)
Language acquisition has always been a challenging process for language learners, particularly adult learners, and thus educators are always looking for interesting and innovative ways to help them learn language effectively. Movies with subtitles have become popular as a resource for language acquisition because they are entertaining, provide visual auditory input, and provide authentic context for the learners. The combination of audio-visual elements such as pictures, videos, sounds, and subtitles in movies contributes many inputs, from learning about history and culture to learning and acquiring the English language. Additionally, motivation plays a crucial role in acquiring a second language. Therefore, this study explores the effect of subtitled movies on English language acquisition among postgraduate students and their learning motivation. The research employed a qualitative method where semi-structured interviews were conducted by interviewing 12 participants, postgraduate students from a local university in Malaysia. The findings revealed that subtitled movies are effective in language learning to improve students' English language skills, particularly in vocabulary expansion and reading skills. Besides, the use of subtitled movies also promotes a positive learning experience where students feel motivated to learn when using subtitled movies. This study demonstrates the potential of subtitled movies as valuable learning material in language learning, suggesting their integration into the education curriculum. This study may contribute to the growing research on the use of subtitled movies in language learning, providing insightful understanding for educators and policymakers in the field of language education.